2019
DOI: 10.1021/acsami.9b11115
|View full text |Cite
|
Sign up to set email alerts
|

Cu4Bi4Se9: A Thermoelectric Symphony of Rattling, Anharmonic Lone-pair, and Structural Complexity

Abstract: Thermoelectric technology, enabling an environmentally friendly direct heat to electricity conversion, provides a possible alternative energy solution. To obtain a higher thermoelectric conversion efficiency, a larger dimensionless figure of merit ZT is required, which is, however, very difficult owing to the mutually restricted and even reversely correlated key property parameters. Herein, we report for the first time the thermoelectric properties of novel Cu 4 Bi 4 S 9 and Cu 4 Bi 4 Se 9 materials with compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…As shown in Figure a,b, the relatively small band gap is an indication of a striking electrical transport property. The measured band gaps of 2 (0.94 eV) and 1 (1.88 eV) agree with the DFT calculations, which are also consistent with those of Cu 4 Bi 4 Se 9 (0.45 eV) and Cu 4 Bi 4 S 9 (0.81 eV) . The electronic structures also depict slightly flattened bands near the Fermi level, indicating a considerably large band effective mass ( m *) (Figure a,b).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As shown in Figure a,b, the relatively small band gap is an indication of a striking electrical transport property. The measured band gaps of 2 (0.94 eV) and 1 (1.88 eV) agree with the DFT calculations, which are also consistent with those of Cu 4 Bi 4 Se 9 (0.45 eV) and Cu 4 Bi 4 S 9 (0.81 eV) . The electronic structures also depict slightly flattened bands near the Fermi level, indicating a considerably large band effective mass ( m *) (Figure a,b).…”
Section: Resultssupporting
confidence: 84%
“…The lattice thermal conductivity (κ lat ) is the only independent parameter to enhance the ZT . Ongoing efforts in phonon blocking engineering, e.g., all-scale hierarchical architectures (point defects, endotaxial precipitates, grain boundaries), solid solution alloying, , and lone-pair anharmonicity, have been proven to effectively reduce κ lat . However, these strategies face the challenge of boosting ZT ; that is, detrimental charge carrier scattering decreases the electrical mobility as well as the repeatability and stability of the materials, which are major concerns in industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are seven phases, CuBiSe 2 (two modifications), , Cu 1.6 Bi 4.8 Se 8 , Cu 1.78 Bi 4.73 Se 8 , Cu 3 BiSe 3 , Cu 6 BiSe 6 , and Cu 4 Bi 4 Se 9 reported in the ternary Cu–Bi–Se system, which feature complex crystal structures. The research on Cu 4 Bi 4 Se 9 demonstrated its low thermal conductivity and good thermoelectric performance originating from its structural features.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of partial occupancy as a function of unit cell volume and average mass per atom. (a) The obtained database of potential candidates of compounds with partial occupancy; (b) the comparison of κlat among common semiconductors (including elemental, I-V-VI2, I2-IV-VI3, I3-V-VI4, I-V-VI2, II2-IV, III-V, IV-VI, V3-VI2 compounds)61 , Zintl compounds62,63 (including CoSb3, CaZn2Sb2, YbZn2Sb2, Ca3AlSb3, Sr3GaSb3,Yb11InSb9, and Yb14MnSb9) and compounds with partial occupancy (including Ag8GeTe6,64 Ba8Ga16Ge30,65 Ba2Sb2Se5,66 Cu4Bi4Se9,67 Cu5FeS4,68 Cu4Sn7S16,69 Cu2SnSe4,70 Ge1Sb4Te7, 71 Zn8Sb7 72 as well as Cu6Te3S, Bi5CuS8 and Cr5Te8). Only some important compounds are named in Figure7b.…”
mentioning
confidence: 99%